Work-Family Balance and University Social Responsibility. Experiences of Women in Management Positions in Chilean Universities - Gaete Quezada, Ricardo (2018)
This research is aimed at analyzing the problem involved in reconciling work and family based on the experience of 10 women who hold management positions in two Chilean universities. A qualitative research approach and a semi-structured interview as the data collection technique were applied. The analysis of the results was performed by means of the procedures proposed by the Grounded Theory, identifying some elements that condition the balance between work and family responsibilities of the academic faculty interviewed. The main conclusion of the study proposes that the non-existence of policies and explicit institutional strategies for reconciliation force women in university executive positions to turn to the private sector for the support needed to carry out their jobs, becoming a barrier that conditions the professional life of the study subjects. Moreover, this aspect represents an important challenge for the strengthening of the universities’ internal social responsibility through concrete actions that allow people who work in these institutions to be able to find a balance between their work and family roles.